Correct use and ease of use of a placebo dry powder inhaler in subjects with asthma and chronic obstructive pulmonary disease. (17th December 2018) - Feldman, Gregory J; Galkin, Dmitry V; Patel, Pinal; Collison, Kathryn A; Sharma, Raj
Correct use and ease of use of a placebo dry powder inhaler was evaluated in two single-arm, United States-multicenter, phase-IV studies in adults with asthma ( n = 259) or chronic obstructive pulmonary disease (COPD; n = 278) who were receiving maintenance inhaler therapy. Subjects demonstrating correct placebo inhaler use within three attempts at screening were instructed to take once-daily inhalations from the inhaler for 28 ± 2 days (continuing usual maintenance), followed by randomization to complete one of two versions of an ease-of-use questionnaire and reassessment for correct inhaler use. At study end, 96% asthma/93% COPD subjects rated the placebo inhaler as "easy" or "very easy" to use while demonstrating correct use. Furthermore, 99% asthma/99% COPD subjects indicated it was "easy" or "very easy" to determine number of doses remaining, and 81%/84%, respectively, indicated they would be "likely" or "very likely" to request their current medication in the inhaler, if available. Adverse event (AE) rates were 12% asthma/15% COPD, most frequently headache (3%/3%). Treatment-related AEs were reported in one subject with asthma (cough) and four subjects with COPD (cough, n = 3; back pain, n = 1). At study end, most subjects with asthma or COPD operated the placebo inhaler correctly and found it easy to use.